2019
DOI: 10.1186/s12871-019-0746-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hypophosphatemia on outcome of patients in intensive care unit: a retrospective cohort study

Abstract: Background Hypophosphatemia generally occurs in Intensive Care Units (ICUs), but its impact is often ignored. The aim of this study was to investigate whether hypophosphatemia can be a risk factor for ICU 28-day mortality. Methods A single-center retrospective cohort study was conducted by collecting data from 1073 patients admitted to general ICU and then presented to the Sixth Affiliated Hospital, Sun Yat-sen University (Guangzhou City, Guangdong Province, China) from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 21 publications
6
60
0
Order By: Relevance
“…Also, they found the timing or the duration of hypophosphatemia had no signi cant association with ICU mortality. Another retrospective cohort study among 946 ICU patients performed by Wang et al's [8] indicated that patients in ICU with hypophosphatemia had higher 28-day ICU mortality (35.3% versus 24%) and longer ICU stay [(5.5, 2.8 to 10.6) versus (1.7, 1.5 to 3.4)]. According to the results of their study, hypophosphatemia was an independent risk factor for 28-day ICU mortality (OR = 1.5, 95%CI 1.1 to 2.1, P = 0.01, adjusted).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, they found the timing or the duration of hypophosphatemia had no signi cant association with ICU mortality. Another retrospective cohort study among 946 ICU patients performed by Wang et al's [8] indicated that patients in ICU with hypophosphatemia had higher 28-day ICU mortality (35.3% versus 24%) and longer ICU stay [(5.5, 2.8 to 10.6) versus (1.7, 1.5 to 3.4)]. According to the results of their study, hypophosphatemia was an independent risk factor for 28-day ICU mortality (OR = 1.5, 95%CI 1.1 to 2.1, P = 0.01, adjusted).…”
Section: Discussionmentioning
confidence: 99%
“…Inorganic phosphate is the value of serum phosphate measured in the clinic [1][2][3][4][5]. Although serum phosphate is very low, it plays an important role in the body [1][2][3][6][7][8][9]. For example, (I) participating in the composition of cell membranes in the form of phospholipids to maintain the integrity and function of the cell structure;…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Severe cases with PO 4 3− depletion may cause symptoms such as fatigue [5], myocardial depression [6], rhabdomyolysis [7], seizures [8], and haemolytic anaemia [9] and, over time, can ultimately contribute to bone abnormalities such as osteomalacia or rickets [10,11]. Rarely, the most severe cases of HP can be fatal [12][13][14]; respiratory muscle dysfunction or impaired myocardial metabolism and decreased cardiac contractility have been associated with severe HP [6,13,15,16]. Hypophosphataemia is a known adverse drug reaction with ferric carboxymaltose (FCM) listed in the Ferinject ® (FCM) Prescribing Information since registration of the product [17], and it is often transient and, in most cases, asymptomatic.…”
Section: Introductionmentioning
confidence: 99%